2021
DOI: 10.3389/fpsyg.2021.631914
|View full text |Cite
|
Sign up to set email alerts
|

The Cognitive Association Between Effortful Self-Control and Decreased Vitality

Abstract: According to the schema model of self-control, individuals’ self-control efforts activate the fatigue/decreased vitality schema. A precondition for this schema activation is that the cognitive concepts of self-control effort and decreased vitality are associated in individuals’ minds. In the present two studies, the existence of such a cognitive association was tested. In Study 1, 133 school students from Switzerland read two similar stories in a random order. In one story, a fictitious individual engaged in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Some authors deny the view that initial self-control detrimentally affects subsequent self-control and cognition (e.g., Carter et al, 2015 ), while others defend it (e.g., Baumeister et al, 2020 ; see also Englert and Bertrams, 2021 ). We believe that discussing and investigating the underlying mechanisms and potential moderator variables regarding situational fluctuations in self-control capacity is an appropriate way forward (e.g., Bertrams, 2020 , 2021 ). In the present study, we found an effect of our manipulation of self-control capacity on worry; however, there might be different ways to interpret it.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors deny the view that initial self-control detrimentally affects subsequent self-control and cognition (e.g., Carter et al, 2015 ), while others defend it (e.g., Baumeister et al, 2020 ; see also Englert and Bertrams, 2021 ). We believe that discussing and investigating the underlying mechanisms and potential moderator variables regarding situational fluctuations in self-control capacity is an appropriate way forward (e.g., Bertrams, 2020 , 2021 ). In the present study, we found an effect of our manipulation of self-control capacity on worry; however, there might be different ways to interpret it.…”
Section: Discussionmentioning
confidence: 99%